PENGARUH RETRIBUSI PASAR DAN RETRIBUSI SAMPAH TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN ENDE - Mogi, Helena; Ismail, Nuraini; Marselina, Apriana (Jurnal Riset Ilmu Akuntansi, 2023)
This study aims (1) to determine the effect of Garbage Retribution on Ende Regency Original Income. (2) to determine the effect of market levies on Ende regency local revenue. This research is a quantitative descriptive research. Data were collected by observation, interviews, documentation and literature study using multiple linear regression analysis techniques. The results of this study indicate that (1) market fees do not have a significant effect on local revenue at the Regional Revenue Agency of Ende Regency. The results of this study are different from previous research conducted by Hermawan (2021). (2) Garbage fees have no significant effect on local revenue at the Regional Revenue Agency of Ende Regency, this is evidenced by the results of tcount > ttable (2.478 <2.13185) with a significance level (0.244 > 0.05). The results of this study are different from previous research conducted by Hermawan (2021).